Solubility and Preferential Solvation of Piroxicam in Neat Solvents and Binary Systems - Castro, Gabriela Tatiana (2018)
The solubilization and solvatochromic behavior of piroxicam (PRX) were analyzed using UV-vis spectroscopy in neat (protic and aprotic) and binary solvent mixtures. The effects of solvent dipolarity/polarizability and solvent?solute hydrogen bonding interactions on the absorption maxima were evaluated by means of the linear solvation energy relationship concept of Kamlet and Taft. This analysis indicated that both interactions play an important role in the position of the absorption maxima in neat solvents. While, the PRX solubility depends on the solute?solvent specific interactions, polarizability and the cohesive forces of the solvent, manifested mainly by means of the Hildebrand?s solubility parameter. Preferential solvation (PS) was studied in 10 binary mixtures. A non-ideal behavior of the wavenumber curve as the function of analytical mole fraction of co-solvent was detected. Index of preferential solvation, as well as the influence of solvent parameters were calculated. The process of dissolution was analyzed in aqueous binary mixtures of ethanol, ethylene glycol and propylene glycol. They were not spontaneous in all proportions, but when water concentration decreases in the mixtures, the process becomes more spontaneous.